SOSIALISASI DAN PELATIHAN PEMBUATAN PERIZINAN SPP-IRT BAGI UMKM KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Bayu Fajar Susanto; Muchlis; Raju Maulana (CV SWA Anugerah, 2023)
This community engagement aims to provide socialization and training to Micro, Small, and Medium Enterprises (MSMEs) in Tembilahan District, Indragiri Hilir Regency, regarding the SPP-IRT (Notification Letter of Household Food Industry) licensing process. Indragiri Hilir Regency, located in Riau Province, Indonesia, has a rapidly growing MSME sector, particularly in the food and beverage production industry. The background of this engagement is based on the challenges faced by MSMEs in Tembilahan District in managing SPP-IRT licenses. Lack of understanding of licensing requirements, complex procedures, and associated costs often hinder MSMEs from obtaining valid licenses. The consequences are limited access to wider markets for MSMEs and the risk of losing consumer trust in their products. To address these issues, this community engagement will provide socialization and training to MSMEs on SPP-IRT licensing requirements and the necessary steps to effectively manage the licensing process. It is expected that with improved understanding and practical guidance provided, MSMEs can enhance their ability to handle licensing procedures, meet established safety and health standards, and gain access to broader markets. The expected outcomes of this community engagement are increased awareness and understanding of SPP-IRT licensing among MSMEs, an increase in the number of MSMEs with valid licenses, and improved product quality. Additionally, it is anticipated that this engagement will contribute to the growth of the MSME sector in Tembilahan District, Indragiri Hilir Regency, as well as local economic development and the welfare of the community.